Fibromialgija in hipermobilnostni sindrom - Kuret, Zala (Rehabilitacija (Ljubljana), 2019)
Background: Many patients in our rehabilitation outpatient clinic are diagnosed with joint hypermobility syndrome (JHS). The aim of our study was to estimate how many of these patients also have fibromyalgia. Methods: We included 243 patients with fulfilled Revised Brighton criteria of JHS in the study group. They were assessed for fibromyalgia according to the 2010 American College of Rheumatology criteria using Widespread Pain Index and Symptom Severity Score. Pain and its interference with function were assessed with Brief Pain Inventory-Short Form (BPI-SF). We also examined a control group of 20 outpatients without JHS for presence of fibromyalgia. Results: The study group comprised 229 women and 14 men, who were 18 to 86 years old. Among them, 161 patients (66 %) fulfilled the criteria for fibromyalgia, 25 (10 %) were borderline cases and 57 (24 %) did not meet the criteria. Estimated population proportion of patients with fibromyalgia among those with JHS was 66 % (95 % confidence interval 60 % to 72 %). The average number of fulfilled criteria for JHS did not increase with the degree of fibromyalgia. Duration of pain and the number of fulfilled JHS criteria were not correlated to the BPI-SF scores. The proportion of patients with fibromyalgia did not differ statistically significantly between the study and the control group (p = 0.772). Conclusions: Patients with JHS often suffer from wide-spread chronic pain and very often fulfil diagnostic criteria for fibromyalgia. Screening this population is important for preventative measures.
Keywords: chronic pain; Ehlers - Danlos syndrome; Ehlers-Danlos Syndrome; fibromialgija; Fibromyalgia; hipermobilnostni sindrom; joint hypermobility syndrome; kronična bolečina; rehabilitacija; rehabilitation; sindrom Ehlers - Danlos; vocational rehabilitation